Pemberian Terapi Brain Gym terhadap Tingkat Kecemasan dan Stres dalam Pembelajaran Daring pada Siswa - Ibrahim, Afifudin; Wahyudi, Andri Setiya; Tristiana, Rr Dian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of brain gym on anxiety and stress levels in the experimental and control groups. The design of this study is Quasi-Experimental Design using simple random sampling techniques. Based on the results, there was a significant difference in the provision of Brain Gym on anxiety and stress levels in grade X students in the experimental group. From the Wilcoxon Signed Rank Test analysis, the p-value is 0.000. The Mann Whitney Test statistical test obtained the result p-value of 0.000. The results of the study concluded that there was an effect of Brain Gym on anxiety and stress levels in online learning in grade X students. Keywords: Anxiety, Brain Gym, Online Learning, Stress